Trait anger and negative interpretation bias in neutral face perception - Rohrbeck, Pauline; Kersting, Anette; Suslow, Thomas (Frontiers in Psychology, 2023)
Anger is a basic emotion helping people to achieve goals by preparing the body for action and prompting others to change their behavior but is also associated with health issues and risks. Trait anger, the disposition to experience angry feelings, goes along with an attribution of hostile traits to others. Negative distortions in the interpretation of social information have also been observed in anxiety and depression. The present study examined the associations between components of anger and negative interpretation tendencies in the perception of ambiguous and neutral schematic faces controlling for anxiety, depressed mood, and other variables. A sample of 150 young adults performed a computer-based perception of facial expressions task and completed the State-Trait Anger Expression Inventory (STAXI-2) along with other self-report measures and tests. Trait anger and anger expression correlated with the perception of negative affects in neutral but not in ambiguous faces. More specifically, trait anger was linked to the attribution of anger, sadness, and anxiety to neutral faces. Trait anger predicted perceived negative affects in neutral faces when adjusting for anxiety, depression, and state anger. For neutral schematic faces, the present data support an association between trait anger and negatively biased interpretation of facial expression, which is independent of anxiety and depressed mood. The negative interpretation of neutral schematic faces in trait angry individuals seems not only to comprise the attribution of anger but also of negative emotions signaling weakness. Neutral schematic facial expressions might be useful stimuli in the future study of anger-related interpretation biases.